The Implementation of Culture and Literature Through Mambere Tungkot in Simalungun Batak and Mere Ciken in Karo Batak: The Local Wisdom Maintenance - Girsang, M; Sembiring, M (KnE Social Sciences, 2018)
Mambere Tungkot, Duda-Duda, and Sulang Sulang Pahompu (MTDSP) and Mere Ciken ras Tuk-Tuk (MCT) are two forms of traditional ceremonies from Simalungun Batak and Karo Batak Tribes as the local wisdoms. Eventhough the terms are different, they have some similarities purposes. MTDSP and MCT are the traditions which are organized by children and grandchildren toward their parents as the forms of respect and appreciation whom had guided, educated, and given them good lives. In gathering the data, the researcher uses descriptive qualitative method. The objectives of the study are to construct the implementation of literature, such as umpasa ‘poem’ and umpama ‘proverb’ and anding andingen ‘proverb’, philosophy, then to analyze them by conducting hermeneutics theory and methology. The implementation of the roles of the Tolu Sahundulan (the kindships in Simalungunese clan), and the Rakut Sitelu (the kindships in Karonese clan) can be seen through the MTDSP and MCT; how the children and the grandchildren show their love, appreciation, and care toward their parents. By keeping do both the MTDSP and MCT, the local wisdoms from Simalungun, and Karo are still maintained. Keywords: culture, literature, local wisdom, mambere tungkot, mere ciken.